СОЦИАЛЬНАЯ СРЕДА И ЧЕЛОВЕЧЕСКАЯ СУДЬБА В РАННИХ ТРАГЕДИЯХ ГУСЕЙНА ДЖАВИДА - Джахангирзаде, С. (Journal of Oriental Studies, 2016)
Аса көрнекті романтик-ақын Гусейн Джавид Азербайжан әдебиетіне ұлы трагик ретінде енді. Джалил Мамедкулизаденің «Чайный сервиз» атты бір актілі өлеңмен жазылған пьесасы бола тұрса да, әдебиетшілер Г. Джавидті өлеңмен жазылған драманың негізін салушы ретінде санайды. Мақала Г. Джавидтің ерте- ректе жазылған трагедияларындағы әлеуметтік орта мен адам тағдыры туралы. The article deals with the early tragedies of the known playwright and the poet of Azerbaijan – H.Javid, which differ depth of philosophical thought and are classics of the Azerbaijan literature. H. Javid’s tragedies- "The Satan", " Maral", "Lame Timur" differ art expression of ideas of humanism. The philosophical and ethical position of the author in the approach to a theme in "Mother" which based a genre of poetic tragedy in the Azerbaijan dramatic art is in this respect rather significant.